The Development of Cybercrime as a Criminal Offense in the Digital Era and Its Impact on Society (Discourse Journal on Law and Society, 2025)
The development of information technology has brought about significant changes in the social, economic, and legal life of global society. On the one hand, digitalization creates efficiency and convenience in various activities, such as financial transactions, communications, and access to information. However, on the other hand, this progress has also given rise to a new form of crime known as cybercrime. Cybercrime differs from conventional crime in that it is committed through electronic systems that can cross national borders and involve a large number of victims. This crime encompasses various forms, such as data hacking, online fraud, and malware distribution. This research aims to examine the development of cybercrime as a form of modern crime in the digital era and to assess the response of Indonesian criminal law to these challenges. The method used is normative legal, with a statutory, conceptual, and case study approach. This research also examines existing regulations, such as Law Number 11 of 2008 concerning Electronic Information and Transactions (ITE) and Law Number 27 of 2022 concerning Personal Data Protection, in addressing cybercrime issues. The research results show that although Indonesia has several regulations related to cybercrime, their implementation still faces various obstacles. Some of the main obstacles include suboptimal law enforcement, limited technology and human resources, and low levels of public digital awareness. Therefore, regulatory reform, institutional capacity development, and increasing public digital literacy are essential. This is part of a national strategy to address cybercrime comprehensively and sustainably, in order to create a safer and more trustworthy digital environment.